Liberdade com responsabilidade na relação com o outro: contribuições da filosofia para a formação ética dos estudantes no ensino fundamental - Viana, Estêvão Marcos Queiroz (2023)
Today's Brazilian society has increasingly demanded the debate around ethics. Issues such as honesty and justice are always latent. People’s actions are daily called into question, as we daily deal with problems related to violence, corruption and the lack of humanity towards the other. Such issues are especially worrying when it comes to basic education students, mainly elementary school students, who, during their school life, are urged to learn and experience moral and social values in a standardized way, which often prevents them from reflecting about his existence in the world and his own actions. In this sense, the issue of freedom with responsibility and ethical commitment is imposed. To address this issue, we take the thinking of the philosopher Jean-Paul Sartre as a theoretical basis. For him, human beings relate to each other in a committed way, without intermediaries and determinations; they are beings of reciprocity. This reciprocity refers to the ethical commitment, which cannot be intermediated. Therefore, alterity in Sartre is eminently ethical. Taking these considerations into account, the general objective of this research is to investigate whether, in the teaching of philosophy at the fundamental level, Sartre’s thought regarding the conceptions of freedom and responsibility, as a syllabus, can provide young people with elements for reflection around their choices, to the point of leading them to autonomous and citizen actions, contributing to their ethical formation. As specific objectives, we have: i) historically contextualize existentialism according to JeanPaul Sartre, its repercussion, its vision of intellectuality and engagement in social struggles, having as a guiding principle the concept of freedom together with underlying concepts, such as responsibility , action, bad faith and anguish; ii) reflect on the ethical commitment according to Sartre, as a universal responsibility, and the contributions of education and the teaching of philosophy to the ethical behavior of students; iii) analyze the contribution to the reflection of young people around free and responsible action, based on a training group with students in the last year of elementary school and, finally, iv) verify the learning of the concepts by the students involved in the group of training. Thus, our problem-question is the following: is it possible that philosophy at a fundamental level contributes, especially when we rescue Sartre’s concepts of freedom and responsibility, elements for a reflection of young people around their ethical and citizenship formation? We used the action-research methodology, from the perspective of a training group carried out through the following steps: 1) awareness, in which we sought to draw students’ attention to the theme “freedom with responsibility”, from the perspective of Sartrean existentialism ; 2) problematization, in which we propose the debate of philosophical problems from the concrete situations visualized in the film Writers of Freedom; 3) conceptualization, based on the debate generated by a reading workshop on an excerpt from Sartre’s work Existentialism is a humanism (1946) and, finally, 4) a final evaluation of the learning of the concepts. Each phase was proposed from the debate raised by the theme “freedom with responsibility” towards the students who proposed to participate in the training group, enrolled in the 9th grade of elementary school in a public school in Pacatuba-CE, a municipality in the metropolitan region of Fortaleza. Each phase ended with a written questionnaire, which served us to collect qualitative data. Thus, we adopted qualitative data collection and the dialectical method to debate and build syntheses on the issues addressed. As a result of the research, we can say that knowledge involving the concepts of freedom and responsibility, proposed by Sartre, can make learning more meaningful for students, in order to make them reflect on their own actions, in a view of a climate of reciprocity and engagement.